Study on decision making model on information presentation by client’s management: an experimental test on halo and recency effect - Intiyas Utami; Sutarto Wijono (Journal of Economics, Business, and Accountancy Ventura, 2014)
Auditing is a process to verify financial statements that require a high degree of professional skepticism from auditors. However, auditors individually have cognitive limitation in processing information. Overall assessment potentially leads to halo effect that will influence auditors’ decision making. On the other hand, the sequence and type of information presentation affect primacy and recency effect. Our experimental research design manipulated the information about client (convincing or unconvincing), type of information presentation (step by step and end of sequence), sequence of presentation (positive-negative, negative-positive) and length of information (long and short). The subjects of experiment were students who had taken auditing courses. The results shows that (1) there was higher halo bias when individuals had convincing clients than unconvincing clients, (2) there was halo and primacy effects when individuals had convincing clients and information was presented simultaneously and sequentially, (3) there was halo and primacy effects when individuals had convincing clients and information was presented both with positive-negative and negative-positive sequences and both with short and long series.